2008
DOI: 10.1088/0953-8984/20/31/315010
|View full text |Cite
|
Sign up to set email alerts
|

Coverage dependence of the structure of tetracene on Ag(110)

Abstract: The ordered adsorption structures of tetracene on Ag(110) have been studied by low energy electron diffraction (LEED), scanning tunneling microscopy (STM) and density functional theory (DFT) calculations. At a low coverage, as calibrated with LEED, both p(4 × 4) and c(8 × 4) ordered structures are simultaneously formed on an Ag(110) surface at room temperature. STM images suggest the molecular plane is parallel to the Ag surface with its long molecular axis aligned along the [001] azimuth. DFT optimization r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…In addition, tetracene can also be packed with varying manners depending on the film thickness, for instance, the long molecular axis of tetracene can be aligned along either the [001] or [1][2][3][4][5][6][7][8][9][10] symmetry direction of Ag(110). In special, it was demonstrated that neighboring tetracene molecules were imaged with alternating bright and dim area in STM with high molecular coverage in dense packing in our previous work [16], which was originally assigned to the adsorption height difference induced by the delicate balance between the molecule-substrate and intermolecular interaction, as pointed out by conventional density functional theory (DFT) calculations. However, it has been realized afterwards that, however, the commonly used exchange-correlation functions for electrons, either local density approximation (LDA) or extensions thereof, gradient approximation (GGA) fail to describe the long-range electron correlations (or electron dispersion force) [26,27], namely, the Van der Waals (vdW) interaction, which is found to play a core role in determining the structure and properties of noncovalent or weak bonding molecular network [28].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, tetracene can also be packed with varying manners depending on the film thickness, for instance, the long molecular axis of tetracene can be aligned along either the [001] or [1][2][3][4][5][6][7][8][9][10] symmetry direction of Ag(110). In special, it was demonstrated that neighboring tetracene molecules were imaged with alternating bright and dim area in STM with high molecular coverage in dense packing in our previous work [16], which was originally assigned to the adsorption height difference induced by the delicate balance between the molecule-substrate and intermolecular interaction, as pointed out by conventional density functional theory (DFT) calculations. However, it has been realized afterwards that, however, the commonly used exchange-correlation functions for electrons, either local density approximation (LDA) or extensions thereof, gradient approximation (GGA) fail to describe the long-range electron correlations (or electron dispersion force) [26,27], namely, the Van der Waals (vdW) interaction, which is found to play a core role in determining the structure and properties of noncovalent or weak bonding molecular network [28].…”
Section: Introductionmentioning
confidence: 88%
“…STM experiments were performed in an ultrahigh-vacuum (UHV) variable temperature STM system (VT-STM, Omicron, Berlin, Germany) with a base pressure better than 5.0 × 10 −10 mbar, details can be found elsewhere [16,33]. The clean Ag(110) surface (Mateck) was obtained by cycles of argon sputtering (1200 V at beginning and 800 eV in the end) and post annealing to around 573 K, while the cleanliness was double checked by low energy electron diffraction (LEED), core level photoelectron spectroscopy (Specs 100 spectrometer, Berlin, Germany) and STM measurements (Omicron VT-STM).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the moleculesurface and molecule-molecule interactions are expected to be weak ͑van der Waals type͒ and mainly through their cloud. 10,11 Ordered structures have also been observed for submonolayer amounts of pentacene on both Au͑110͒ ͑Ref. The ͑110͒ surfaces of noble metals have received special attention in this respect.…”
Section: Introductionmentioning
confidence: 97%